2019
DOI: 10.1080/22221751.2019.1682472
|View full text |Cite
|
Sign up to set email alerts
|

Different molecular characteristics and antimicrobial resistance profiles of Clostridium difficile in the Asia-Pacific region

Abstract: Molecular epidemiology of Clostridium difficile infection (CDI) has been extensively studied in North America and Europe; however, limited data on CDI are available in the Asia-Pacific region. A multicentre retrospective study was conducted in this region. C. difficile isolates were subjected to multilocus sequence typing (ST) and antimicrobial susceptibility testing. Totally, 394 isolates were collected from Hangzhou, Hong Kong, China; Busan, South Korea; Fukuoka, Japan; Singapore; Perth, Sydney, Australia; N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
(57 reference statements)
3
17
1
Order By: Relevance
“…In this retrospective study, we collected all C. difficile strains isolated in a general teaching hospital in Shanghai, China over a period of 5 years from September 2014 to August 2019 to investigate the molecular epidemiology and risk factors for the most prevalent genotype infection. Unlike the previously reported predominant clones of C. difficile isolates elsewhere in China, which were ST37, followed by ST54, ST3, ST2, and ST35 (Huang et al, 2009;Hawkey et al, 2013;Luo et al, 2019), we observed that ST81 was the major ST type in Renji Hospital in Shanghai, China for these 5 years, indicating a geographical diversity of molecular typing. Notably, a growing trend of ST81 clone in Beijing has been reported recently (Cheng et al, 2020), while another study on C. difficile colonization in patients admitted to an intensive care unit in Shanghai demonstrated a predominant role of ST81 genotype (Cui et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…In this retrospective study, we collected all C. difficile strains isolated in a general teaching hospital in Shanghai, China over a period of 5 years from September 2014 to August 2019 to investigate the molecular epidemiology and risk factors for the most prevalent genotype infection. Unlike the previously reported predominant clones of C. difficile isolates elsewhere in China, which were ST37, followed by ST54, ST3, ST2, and ST35 (Huang et al, 2009;Hawkey et al, 2013;Luo et al, 2019), we observed that ST81 was the major ST type in Renji Hospital in Shanghai, China for these 5 years, indicating a geographical diversity of molecular typing. Notably, a growing trend of ST81 clone in Beijing has been reported recently (Cheng et al, 2020), while another study on C. difficile colonization in patients admitted to an intensive care unit in Shanghai demonstrated a predominant role of ST81 genotype (Cui et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, pig and calf were thought to be the predominant animals carrying C. difficile isolates. However, such kind of study is quite limited in China, although there are many molecular studies of clinical C. difficile in China, even in the Asia-Pacific area [20,21]. Until now, there is only one report on C. difficile from pig, chicken and duck in China in 2019, but calf was not included [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no any data supporting the standard of CDI diagnosis for children in China. The diversity of individual gut microbiomes was distinctly different among human beings from different geographical regions [47], and stewardship of antimicrobial use was implemented at different [48]. Thus, it was speculated that the principle of CDI test for children under 1 year might be differentiated in China.…”
Section: Discussionmentioning
confidence: 99%